The determinants of very severe immune-related adverse events associated with immune checkpoint inhibitors: A prospective study of the French REISAMIC registry. (November 2021) - Ruste, Valentine; Goldschmidt, Vincent; Laparra, Ariane; Messayke, Sabine; Danlos, Francois-Xavier; Romano-Martin, Patricia; Champiat, Stéphane; Voisin, Anne-Laure; Baldini, Capucine; Massard, Christophe; Laghouati, Salim; Marabelle, Aurélien; et al.
Abstract: Background: Immune-related adverse events (irAEs) remain generally unpredictable, and severe irAEs remain challenging to detect early and manage. Very severe (grade IV–V) irAEs have not been extensively characterised in prospective studies, and their predictive factors remain unknown. Objective: The objective of the study was to describe and identify predictive factors of very severe (grade IV–V) irAEs. Design: The French Registre des Effets Indésirables Sévères des Anticorps Monoclonaux Immunomodulateurs en Cancérologie (REISAMIC) registry has prospectively collected all clinically significant irAEs occurring in patients treated with immune checkpoint inhibitors at Gustave Roussy Institute since 2014. Setting: This was a single-centre prospective cohort study at the Gustave Roussy Institute cancer centre (Villejuif, France). Participants: The participants were all adult patients with a solid or haematological cancer treated with an anti–programmed cell death 1 (PD-1) or an anti–programmed cell death-ligand 1 (PD-L1) and who presented a clinically significant irAE. Main outcomes and measures: The main outcomes included the clinical and laboratory characteristics of patients with very severe irAEs, including tumour type, affected organs, time to irAE occurrence, blood cell count and serum biochemistry parameters. Results: Of the 1187 patients prospectively followed in REISAMIC between December 2014 and January 2020, 380 (32.0%) had at least one irAE, and 34 (2.86%) presented with very severe irAEs (grades IV–V). Among the 380 patients with an irAE, the distribution of very severe irAEs (grades IV–V) was 8.95% and death (grade V) was 3.95%. Among the 34 patients with very severe irAEs, 33 were treated with monotherapy of PD-1 or PD-L1 inhibitors, and one patient was treated with a combination of PD-1 and cytotoxic T-lymphocyte–associated protein 4 inhibitors. The median time to occurrence was shorter for very severe irAEs (median [interquartile range]: 41 days [0–634] for grades IV–V; versus 91 days [0–1123] for grades I–III; p = 0.01680). On initiation of immunotherapy, the predictive factors for very severe irAEs were performance status ≥2, elevated neutrophil/lymphocyte ratio and treatment for lung cancer. Conclusions: Very severe (grade IV–V) immunological toxicities occurred earlier than mild severe toxicities. On initiation of immunotherapy, patients with poor performance status, elevated neutrophil/lymphocyte ratio and lung cancer are identified at risk of developing these very severe toxicities. These results could help to develop risk scores to identify patients at risk of developing severe toxicities. Highlights: Very severe immune-related adverse events (irAEs) are challenging to detect early and manage. Very severe irAEs occurred earlier than mild severe irAEs. The predictive factors for very severe irAEs were performance status ≥ 2 and elevated neutrophil/lymphocyte ratio. The organ most implicated in irAE death was lung with pneumonitis.